Compressive behavior of plastic fiber reinforced concrete - Chai, Wee Kwok (2010)
Concrete is a construction material created by mixing cement, water and aggregates together. It has a relatively high compressive strength but significantly low tensile strength. The aim of this project was to analyze the compressive behavior of concrete due to plastic fiber (Polypropylene). This project focused on the effect of the fiber content and fiber lengths on the strength of the fiber reinforced concrete specimen. The fiber content varies from 1%, 2% and 3% of volume fraction with lengths of 2 cm, 3 cm and 4 cm. The objective is to determine the ideal proportion of length and quantities of fiber needed to improve the compressive strength of the concrete. It can be concluded that the addition of plastic fiber (Polypropylene) does not strengthen the concrete strength. However, the presence of plastic fiber helps to improve the brittleness of concrete specimen without altering much of the concrete strength. Therefore, it is appropriate to add a small percentage of fiber content into concrete. From the experimental results, the ideal combination of fiber content and fiber length is (1%, 2cm).